A CASE OF CENTRAL PRECOCIOUS PUBERTY SECODNARY TO HYPOTHALAMIC HAMARTOMAS WITH GELASTIC SEIZURE - MK, Khanisa; MH, Suhaimi (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Central Precocious Puberty (CPP) is caused by early maturation of the hypothalamic- pituitary-gonadal axis, characterized by sequential development of secondary sexual characteristics before 8 years in girls and 9 years in boys. We reported a case of CPP secondary to Hypothalamic Hamartomas (HH) which was initially referred for sexual precocity. CASE NAI, currently 6 years old, presented with monthly episodes of per vaginal bleeding at 2 months old. There was concurrent breast enlargement associated with peculiar body odor and episodes of inappropriate giggling during infancy. There was positive family history of epilepsy on the paternal side. Physically, NAI is not dysmorphic, appears tall and overweight for age with Tanner staging of B4, A1, P1. There were neither neurocutaneous signs nor virilization of the external genitalia. Basal and stimulated LH, FSH values and ultrasound pelvis showed pubertal values with advancement of bone age noted on bone age assessment. Following this, she was commenced on monthly IM Lucrin injection which showed favorable biochemical and clinical response after 3 months of treatment. An EEG done showed abnormal epileptic records after she developed recurrent episodes of gelastic seizure since May 2016. An MRI of the brain showed the presence of a well define solid/lobulated mass in hypothalamus measuring 2.1 x 2.3 x 2.8 cm, with no mass effect to adjacent structure. An MRI was repeated after 2 years due to uncontrolled seizure despite being on oral Keppra, and showed similar findings as before. CONCLUSION Hypothalamic Hamartomas are rare congenital lesions presenting with classic triad of central precocious puberty, gelastic epilepsy and development delays. CPP responds well to treatment with GNRH agonist. However, gelastic seizure can differ in severity and evolution in different individuals. Majority are resistant to antiepileptics hence our patient may benefit from surgical removal of hamartomas either via transcallosal approach or minimally invasive surgery.